PENDIDIKAN KEWIRAUSAHAAN: MELATIH BERWIRAUSAHA MELALUI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) SISWA SEKOLAH DASAR - Megawati, Megawati; Sawita, Nada; Wahyudi, Luthfi; Firman, Firman (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
Training entrepreneurial skills from an early age is about creating young entrepreneurs and forming individuals with a proactive, confident, independent, and resilient attitude in facing the challenges of the times. So efforts to introduce and train entrepreneurship skills at the basic level are a long-term investment in sustainable social, economic, and individual development. This research uses a qualitative descriptive approach through the literature study method to explain the implementation activities of the P5 project in training entrepreneurship skills for students in elementary schools. Data collection was collected by collecting references from various sources relevant to the research topic. Data analysis was carried out by critically and deeply examining the library sources that had been obtained, then synthesizing and concluding. This research shows that the P5 project with the theme of entrepreneurship is a forum for entrepreneurship training activities for students. Entrepreneurship activities in elementary schools are very varied, including market day, culinary corner, bazaar, cooking day, trade stand, and work title. This activity encourages students to practice becoming entrepreneurs and instills independent, creative, innovative, and tough characters in students. So, it can be concluded that the P5 project with the theme of entrepreneurship at the elementary school level not only introduces the concept of entrepreneurship and teaches basic entrepreneurial skills but also focuses more on cultivating positive attitudes or characters towards entrepreneurship from an early age.